CIVIL SOCIETY IN RUSSIA: CURRENT TRENDS OF THE DEVELOPMENT - Batanina, Irina; Lavrikova, Anastasiya; Pukhanov, Sergey; Shumilova, Olga (Revista Inclusiones, 2019)
The article deals with the analysis of the condition and dynamics of the development of civil society in Russia based on the materials of monitoring researches which were conducted at the Laboratory of socio-political researches of Tula State University in 2017-2019. The peculiarities of participation of citizens and public organizations in socio-political life, their needs and contentment with an interaction in the system “authority – society” are single out. The perspectives of improving the existing mechanisms of the non-for-profit sector development are determined in the context of the regional specificity. The authors’ objective was to study the demands and contentment with an interaction “authority – society” in order to work out recommendations on improvement of the existing mechanisms of the non-for-profit sector development.